2021
DOI: 10.1186/s13018-020-02114-6
|View full text |Cite
|
Sign up to set email alerts
|

Mir-573 regulates cell proliferation and apoptosis by targeting Bax in human degenerative disc cells following hyperbaric oxygen treatment

Abstract: Background MicroRNA (miRNA) plays a vital role in the intervertebral disc (IVD) degeneration. The expression level of miR-573 was downregulated whereas Bax was upregulated notably in human degenerative nucleus pulposus cells. In this study, we aimed to investigate the role of miR-573 in human degenerative nucleus pulposus (NP) cells following hyperbaric oxygen (HBO) treatment. Methods NP cells were separated from human degenerated IVD tissues. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…It has been reported that HBO treatment induces lncRNA-MALAT1 to target miR-92a/KLF2 for angiogenesis after myocardial infarction [21]. HBO treatment suppressed the degeneration of nucleus pulposus cells via miR-107 and miR-573 [19,20]. In the current study, we found that HBO treatment suppressed the activation of NLRP3-dependent pyroptosis signaling in NSCs following OGD by downregulation of lncRNA-H19.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…It has been reported that HBO treatment induces lncRNA-MALAT1 to target miR-92a/KLF2 for angiogenesis after myocardial infarction [21]. HBO treatment suppressed the degeneration of nucleus pulposus cells via miR-107 and miR-573 [19,20]. In the current study, we found that HBO treatment suppressed the activation of NLRP3-dependent pyroptosis signaling in NSCs following OGD by downregulation of lncRNA-H19.…”
Section: Discussionsupporting
confidence: 62%
“…HBO treatment not only enhances the viability and survival of NSCs but also enhances NSC proliferation and differentiation into neurons after ischemic injury [16][17][18]. Recent studies have proven that HBO exerts therapeutic roles in various pathophysiologies of hypoxic/ischemic diseases by regulating noncoding RNA [19][20][21]. In this present study, an OGD exposure and HBO treatment model of NSCs in vitro was established with a purpose to investigate the effect and mechanism of HBO treatment on the presumed lncRNA-H19-associated pyroptosis of NSCs following OGD and clarify its influence on NSC proliferation and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the overexpression of miR-573 following HBO inhibited apoptosis and enhanced proliferation. As in the preceding study, transfection with an antagonist of miR-573 partly suppressed the effects of HBO [ 67 ].…”
Section: Hyperbaric Oxygen and Regenerationmentioning
confidence: 65%
“…Importantly, miRNAs influencing the activity of the Wnt pathway, e.g., mir-128, mir-148, mir-151a, mir-181a, mir-181b, mir-374a, or mir-376c-3p, can also regulate apoptosis ( 55 , 58 , 67 ). Mir-573, upregulated after HBOT, was responsible for the repression of Bax mRNA, consequently cleaved forms of caspase-3 and caspase-9 were also decreased ( 74 ).…”
Section: The Effects Of Hbo Treatment In Experimental Hypoxia-ischemiamentioning
confidence: 99%